Artistic Experiments in Expanded Animation: Combining 3D Printing with Virtual Reality To Create Anamorphic Shadow Animations (International Journal on Stereo & Immersive Media, 2025)
This paper explores the integration of Virtual Reality, 3D printing, and anamorphic shadow techniques in the field of Expanded Animation. Using a collaborative and experimental Artistic Research method, the study contributes to extending the boundaries of animation, and to attributing a stronger sense of agency to the spectator or ‘eccentric observer’. The paper discusses different iterations in the development of the ‘Anamorphotrope’, an original installation work that has been exhibited in two modalities: as a VR installation and as a 3D-printed zoetrope. Both on a technical and conceptual level the novel approach taken in this project has a number of implications for future practices in animation and related artistic fields.